Results of Surgical Treatment for Fractures of the Lower End of the Humerus - Mine, Hiroko; Kutsuna, Tatsuo; Ashihara, Ai (Orthopedics & Traumatology, 1997)
Thirty-eight cases with fractures of the lowerend of the humerus who were treated surgically were studied. Subjects consisted of 26 males, 12 females with a mean age of 7.4 years. The follow-up period ranged seven to 63 months. No ROM restriction of the elbow was found in patients aged undertwenty years, however only 4 cases restriction in their ROM. Valgus deformity of the elbow was observed in 2 cases, and varus deformity in 4 cases. Bony union was achieved in all cases